KEBIJAKAN KAPOLRESTABES SEMARANG DALAM MENANGANI PREMANISME DI KOTA SEMARANG - Purwoto, Mangiring Silalahi, Nyoman Serikat Putra Jaya, (Program Studi S1 Ilmu Hukum, Fakultas Hukum, Universitas Diponegoro, 2012)
Thugs in daily life is the man who wants to be free, life does not want to set up sometimes filled with violence, and does not care about norms and ethics in publik life. Effects of bullying in Indonesia , especially in Semarang is the fear that arises in society. In other words thuggery will always disrupt security and public order. Semarang Polrestabes therefore must be able to handle the problem of gangssterism. Semarang Kapolrestabes Policy in dealing with the problems of gangsterism in the city of Semarang done by several measure, which fall into two steps, namely preventive and repressive measures. In carrying out such a move can not be separated from Semarang Polrestabes obstacles. Therefore the assistance of an outside party is expected.